Unpacking the black box of successful ICT-enabled service transformation: how to join up the vertical, the horizontal and the technical. Issue 1 (2nd January 2016) - Eppel, Elizabeth; Lips, Miriam
Abstract : This paper aims to understand what goes on in the black box of successful, joined-up ICT-enabled service transformation, where complex interactions and integration must occur among the horizontal processes internal to a joined-up service delivery network, the vertical top-down processes of the organizations involved, and the change processes caused by using ICTs. A new conceptual framework is developed and applied to an illustrative case study of successful, joined-up service transformation in New Zealand.